2019
DOI: 10.3389/fimmu.2019.00204
|View full text |Cite
|
Sign up to set email alerts
|

IL-26, a Cytokine With Roles in Extracellular DNA-Induced Inflammation and Microbial Defense

Abstract: Interleukin 26 (IL-26) is the most recently identified member of the IL-20 cytokine subfamily, and is a novel mediator of inflammation overexpressed in activated or transformed T cells. Novel properties have recently been assigned to IL-26, owing to its non-conventional cationic, and amphipathic features. IL-26 binds to DNA released from damaged cells and, as a carrier molecule for extracellular DNA, links DNA to inflammation. This observation suggests that IL-26 may act both as a driver and an effector of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 97 publications
2
70
0
1
Order By: Relevance
“…We found cytokine production and phenotypic profiles to be mostly similar for expanded CB Tregs versus APB Tregs (Figure 5 and Figure 6, blue and orange) and for expanded CB Tconv versus APB Tconv (Figure 5 and Figure 6, green and red) with the most dramatic differences observed between Tregs and Tconv, regardless of the source (CB or APB). Expectedly, CB and APB Treg produced limited pro-inflammatory and effector cytokines ( Figures 5A-H) relative to Tconv (103)(104)(105)(106)(107)(108), and though we observed no differences in the production of immunosuppressive or effector Treg-associated cytokines (109,110) between the two subsets ( Figures 5I-K), we did observe APB Treg to produce increased IL-2 relative to CB Treg (Figure 5L). This could be indicative of non-Treg contaminants, consistent with known Treg reliance on exogenous IL-2 (111).…”
Section: Expanded Cb Tregs Exhibit a Highly Activated And Suppressivementioning
confidence: 65%
“…We found cytokine production and phenotypic profiles to be mostly similar for expanded CB Tregs versus APB Tregs (Figure 5 and Figure 6, blue and orange) and for expanded CB Tconv versus APB Tconv (Figure 5 and Figure 6, green and red) with the most dramatic differences observed between Tregs and Tconv, regardless of the source (CB or APB). Expectedly, CB and APB Treg produced limited pro-inflammatory and effector cytokines ( Figures 5A-H) relative to Tconv (103)(104)(105)(106)(107)(108), and though we observed no differences in the production of immunosuppressive or effector Treg-associated cytokines (109,110) between the two subsets ( Figures 5I-K), we did observe APB Treg to produce increased IL-2 relative to CB Treg (Figure 5L). This could be indicative of non-Treg contaminants, consistent with known Treg reliance on exogenous IL-2 (111).…”
Section: Expanded Cb Tregs Exhibit a Highly Activated And Suppressivementioning
confidence: 65%
“…IL-26 stimulates neutrophils and accumulates immune cells against bacteria in human lung infections [20]. Recently, IL-26 was regarded as a critical cytokine for extracellular DNA-induced inflammation and bacterial infection [21,22]. IL-26 can be rapidly induced by IL-1β in Th17 Cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…The control of innate immunity in human lungs is complex, probably because of its fundamental importance for host survival. 14 IL-26 may act both as a driver and an effector of inflammation, leading to the establishment of a deleterious amplification loop and ultimately, sustained inflammation as reported by Larochette et al 15 IL-26 is involved in the immune response to bacterial endotoxin in the airways of healthy human subjects. 16 Experimental studies demonstrated in vivo a direct anti-microbial effect of IL-26 against extracellular bacteria.…”
Section: Introductionmentioning
confidence: 89%